WHAT IS CHINA TO US? - A. D. Voskressenski (Сравнительная политика)
Foreword by the Editor-in-Chief and founder of the journal Comparative Politics Russia to special issues: “China as a Global Factor: A Comparative Analysis of Responses” and “Contemporary International Relations: Theory and Practice of Comparative Analysis of Responses to External and Internal Challenges” explaining the structure of the journal issues and the logic of interconnection between published articles within the journal.